Surfactant-free synthesis of copper nanoparticles and gas phase integration in CNT-composite materials. Issue 3 (6th January 2021) - Brunet, Paul; McGlynn, Ruairi J.; Alessi, Bruno; Smail, Fiona; Boies, Adam; Maguire, Paul; Mariotti, Davide
Abstract : Surfactant free synthesis of copper nanoparticles by using atmospheric plasma pressure. Abstract : Copper nanoparticles (Cu-NPs) represent a viable low-cost alternative to replace bulk copper or other more expensive NPs ( e.g. gold or silver) in various applications such as electronics for electrical contact materials or high conductivity materials. This study deals with the synthesis of well dispersed Cu-NPs by using an Ar + H2 microplasma using a solid copper precursor. The morphological analysis is carried out by electron microscopy showing particles with a mean diameter of 8 nm. Crystallinity and chemical analyses were also carried out by X-ray diffraction and X-ray photoelectron spectroscopy, respectively. In the second step, the Cu-NPs were successfully deposited onto porous carbon nanotube ribbons; surface coverage and the penetration depth of the Cu-NPs inside the CNT ribbon structure were investigated as these can be beneficial for a number of applications. The oxidation state of the Cu-NPs was also studied in detail under different conditions.